Gender, Race and Parenthood Impact Academic Productivity During the COVID-19 Pandemic: From Survey to Action - Staniscuaski, Fernanda; Kmetzsch, Livia; Soletti, Rossana C.; Reichert, Fernanda; Zandonà, Eugenia; Ludwig, Zelia M. C.; Lima, Eliade F.; Neumann, Adriana; Schwartz, Ida V. D.; Mello-Carpes, Pamela B.; Tamajusuku, Alessandra S. K.; Werneck, Fernanda P.; et al. (Frontiers in Psychology, 2021)
The coronavirus disease 2019 (COVID-19) pandemic is altering dynamics in academia, and people juggling remote work and domestic demands – including childcare – have felt impacts on their productivity. Female authors have faced a decrease in paper submission rates since the beginning of the pandemic period. The reasons for this decline in women’s productivity need to be further investigated. Here, we analyzed the influence of gender, parenthood and race on academic productivity during the pandemic period based on a survey answered by 3,345 Brazilian academics from various knowledge areas and research institutions. Productivity was assessed by the ability to submit papers as planned and to meet deadlines during the initial period of social isolation in Brazil. The findings revealed that male academics - especially those without children - are the least affected group, whereas Black women and mothers are the most impacted groups. These impacts are likely a consequence of the well-known unequal division of domestic labor between men and women, which has been exacerbated during the pandemic. Additionally, our results highlight that racism strongly persists in academia, especially against Black women. The pandemic will have long-term effects on the career progression of the most affected groups. The results presented here are crucial for the development of actions and policies that aim to avoid further deepening the gender gap in academia.